The letters of Mina Harker - Bellamy, Dodie ca. 20./21.Jh (Semiotext(e), 2021)
"First published in 1998, Dodie Bellamy's debut novel The Letters of Mina Harker sought to resuscitate this minor character from Bram Stoker's Dracula and reimagine her as an independent woman living in San Francisco during the 1980s--a woman not unlike Dodie Bellamy. Harker confesses the most intimate details of her relationships with four different men in a series of letters. Vampirizing Mina Harker, Bellamy turns the novel into a laboratory: a series of attempted transmutations between the two women in which the real story occurs in the gaps and the slippages. Lampooning the intellectual theory-speak of that era, Bellamy's narrator fights to inhabit her own sexuality despite feelings of vulnerability and destruction."--Page 4 of cover
Keywords: Bellamy, Dodie / Fiction; Man-woman relationships / Fiction; Vampires / Fiction; Women / California / Fiction; San Francisco (Calif.) / Fiction; California / Fiction; Relations entre hommes et femmes / Romans, nouvelles, etc; Vampires / Romans, nouvelles, etc; Californie / Romans, nouvelles, etc; California / San Francisco; 1900-1999; Epistolary fiction; Fiction; History; Erotic fiction; Fiktionale Darstellung